2016
DOI: 10.4162/nrp.2016.10.5.487
|View full text |Cite
|
Sign up to set email alerts
|

KoreanCurcuma longa L. induces lipolysis and regulates leptin in adipocyte cells and rats

Abstract: BACKGROUND/OBJECTIVESTurmeric (Curcuma longa L.) has been reported to have many biological functions including anti-obesity. Leptin, peptide hormone produced by adipocytes and its concentration is increased in proportion to the amount of the adipocytes. In the present study, we examined the effects of Korean turmeric on the regulation of adiposity and leptin levels in 3T3-L1 adipocytes and rats fed a high-fat and high-cholesterol diet.MATERIALS/METHODSLeptin secretion, free fatty acid and glycerol contents in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 39 publications
1
13
1
1
Order By: Relevance
“…Leptin activates inflammatory cytokine release, including IL-1a, IL-1b, IL-6, and TNF-α, that in turn modulates the immune response (Lord et al, 1998). Adiponectin and gherelin are also important in appetite and energy homeostais, and curcumin has been shown to cause adipokine release from adipocytes (Panahi et al, 2016b), inducing lipolysis that may affect leptin (Song and Choi, 2016). It has been suggested that curcumin may increase ghrelin levels through its antioxidant actions (Xu et al, 2013); however, how curcumin modulates the interplay between leptin, adiponectin, and gherelin needs clarification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leptin activates inflammatory cytokine release, including IL-1a, IL-1b, IL-6, and TNF-α, that in turn modulates the immune response (Lord et al, 1998). Adiponectin and gherelin are also important in appetite and energy homeostais, and curcumin has been shown to cause adipokine release from adipocytes (Panahi et al, 2016b), inducing lipolysis that may affect leptin (Song and Choi, 2016). It has been suggested that curcumin may increase ghrelin levels through its antioxidant actions (Xu et al, 2013); however, how curcumin modulates the interplay between leptin, adiponectin, and gherelin needs clarification.…”
Section: Discussionmentioning
confidence: 99%
“…Investigative clinical trials have suggested that curcumin has antioxidant (Panahi et al, 2016a;Sahebkar et al, 2015b), antiinflammatory (Panahi et al, 2012;Sahebkar, 2014a), and immunomodulatory (Ghandadi and Sahebkar, 2017;Karimian et al, 2017;Ganjali et al, 2014) properties and is effective in a wide number of diverse conditions including osteoarthritis and rheumatoid arthritis (Kurien et al, 2015;Panahi et al, 2014c;Sahebkar and Henrotin, 2016), metabolic syndrome (Inzaugarat et al, 2017;Panahi et al, 2015b;Panahi et al, 2014b;Sahebkar, 2013;Rahmani et al, 2016), cancer (Deng et al, 2016;Teymouri et al, 2017;Mirzaei et al, 2016;Momtazi et al, 2016), dyslipidemia (Panahi et al, 2016c;Sahebkar, 2014b;Ganjali et al, 2017), chronic obstructive pulmonary disease (Lelli et al, 2017;Panahi et al, 2014a), and anxiety and depression (Esmaily et al, 2015;Panahi et al, 2015a). Curcumin has a direct effect on adipokine release from adipocytes (Panahi et al, 2016b;Hajavi et al, 2017) with the suggestion that it may induce lipolysis and regulate leptin in animals (Song and Choi, 2016). Data suggest that there is an effect on leptin receptor gene expression (Nejati-Koshki et al, 2014b;Nejati-Koshki et al, 2014a) and that interruption of the leptin signaling pathway with a fall in leptin levels decreases advanced glycation end-products (Tang and Chen, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Song and Choi (2016), treatment of 3T3-L1 adipocytes with 10 µg/mL turmeric extracts for 24 h resulted in significantly reduced lipid accumulation and leptin levels, while the levels of free fatty acids and glycerol were increased [61]. In addition, turmeric treatment increased adipose triglyceride lipase and hormone-sensitive lipase mRNA levels, suggesting increased triglyceride degradation ( Table 1) [61].…”
Section: Effects Of Curcumin: In Vitro Adipocyte Studiesmentioning
confidence: 98%
“…An increase in the number of adipocytes (hyperplasia) due to adipocyte differentiation and an increase in the size of adipocytes (hypertrophy) are both contributors to the development of obesity (Guo et al, 2015;Shepherd et al, 1993;Spalding et al, 2008). An increase in adipose tissue mass is paralleled by higher prevalence of obesity-related complications, such as hyperlipidemia, hypertension, type 2 diabetes, and nonalcoholic fatty liver disease (Kopelman, 2000;Spalding et al, 2008). An improved understanding of adipocyte differentiation and function is critical to accelerate the development of drugs for the treatment of obesity and its complications.…”
Section: Introductionmentioning
confidence: 99%